Spatial and temporal scaling in habitat utilization by klipspringers (Oreotragus oreotragus) determined using giving-up densities - DRUCE, DAVE J; BROWN, JOEL S; KERLEY, GRAHAM I.H; KOTLER, BURT P; MACKEY, ROBIN L; SLOTOW, ROB (Austral ecology, 2009)
An animal's pattern of habitat use can reveal how different parts of its environment vary in quality based on the costs (such as predation risk) and benefits (such as food intake) of using each habitat. We studied klipspringer habitat use in Augrabies Falls National Park, South Africa using giving-up densities (GUDs; the amount of food remaining in a resource patch following exploitation) in experimental food patches. We tested hypotheses related to how salient habitat variables might influence klipspringers' perceptions of foraging costs. At small spatial scales (3-4 m), klipspringer GUDs did not vary with cover and open microhabitats, or with the four cardinal aspects (shading) around shrubs. Adding water adjacent to food patches did not influence GUDs, showing that water is not a limiting complementary resource to food. Generally, klipspringers do not appear to be physiologically constrained. There was no difference in GUDs between four daily time periods, or between summer and winter; however, a significant interaction effect of time-of-day with season resulted from GUDs during the midday time period in winter being significantly higher (perceived value lower) than during the same time period in summer. At moderate spatial scales (10-60 m), klipspringer GUDs increased with distance from rocks because of increased predation risk. Based on GUDs collected at the largest scale (two 4.41-ha grids), klipspringers preferred foraging at greater distances from drainage lines and on pebble and cobble substrates. Overall, this study has shown the efficacy of measuring GUDs to determine klipspringers' habitat utilization while foraging.